STUDENTS’ PERCEPTIONS ON THE USE OF DUOLINGO AS GAMIFICATION TOWARD THEIR VOCABULARY MASTERY AT MTS AK-FAKHRIYAH BATURAJA - Lisda Aryanti; Merie Agustiani; Nurul Afifah (LEAD (Language, Education and Development), 2026)
The purpose of this study was to investigate the attitudes of eighth-grade students at MTs Al-Fakhriyah Baturaja toward the usage of Duolingo as a gamified learning tool to help them acquire their vocabulary. The research used a descriptive qualitative approach. Purposive sample of the eighth-grade population at MTs Al-Fakhriyah Baturaja yielded 21 students from class VIII-B. Data were gathered by a closed-ended questionnaire and open-ended interviews. The questionnaire data were analyzed using a percentage-based approach, whereas the interview data were investigated using Miles and Huberman's (2014) interactive model, which includes data reduction, data display, and conclusion drafting. The data revealed that students had a positive view of Duolingo's ability to help them acquire vocabulary. They found the application to be engaging, interactive, and successful in aiding their comprehension, retention, and application of new language. Furthermore, Duolingo's gamification features, such as points, levels, and prizes, were thought to improve students' motivation, engagement, and confidence in learning English. These findings suggest that gamified tools, such as Duolingo, can promote a more student-centered and motivating vocabulary learning experience.